Tingkat kondisi fisik siswi yang mengikuti ekstrakurikuler bola volli - Saputra, Oji; Achmad, Irfan Zinat; Gani, Ruslan Abdul (Jurnal Porkes, 2023)
The problem with this research is that physical conditions are very low and there are differences in the physical conditions of students participating in volleyball extracurriculars. The aim of this research is to determine the level of physical condition and differences in the physical condition of female students who take part in extracurricular volleyball. The method in this research is a quantitative approach. Population 30 students of Man 3 and 22 SMAN 1. Determination of non-probability sampling using purpose sampling technique. The research instruments used in this research were tests and measurements of physical condition. Data analysis techniques are descriptive statistical tests, normality tests, homogeneity tests, hypothesis tests. The research results showed that there was an average (mean) of 75.54 for MAN 3 and 78.23 for SMAN 1, with a difference of 2.72, and there was no significant difference between the physical conditions of female students who took part in extracurricular volleyball based on the results of data analysis. and test prerequisites. Having an average frequency distribution value with a class interval of 76-80 totaling 11 in the high category for MAN 3 Karawang and SMAN 1 Cabangbungin having an average frequency distribution value with a class interval of 73-78 totaling 8 in the low category. It was concluded that there was no significant difference between the physical conditions of female students who took part in volleyball extracurriculars.